Differential root and shoot responses in the metabolism of tomato plants exhibiting reduced levels of gibberellin - Martins, Auxiliadora O.; Omena-Garcia, Rebeca P.; Oliveira, Franciele S.; Silva, Welder A.; Hajirezaei, Mohammad-Reza; Vallarino, José G.; Ribeiro, Dimas Mendes; Fernie, Alisdair R.; Nunes-Nesi, Adriano; Araújo, Wagner L. (Environmental and Experimental Botany, 2019)
The ability to adapt to the environment is crucial for plant survival and thus a refined communication system capable of integrating endogenous and exogenous signals and further relaying this information to different parts of the plant is a key component of such adaptability. Given that they grow in highly distinct environments it is arguably unsurprising that roots and shoots display different responses to a given environmental condition. Accordingly, a higher sensitivity of roots to gibberellins (GAs) allows rapid adjustments in growth and development possibly triggering (a) stress tolerance mechanism(s). Here we investigated the differential metabolic responses between root and shoot following reductions of the endogenous GA content using tomato (Solanum lycopersicum L.) plants deficient in GA biosynthesis (gib3, moderately deficient, gib2, intermediate deficiency and gib1, extremely deficient in GAs). GA depletion impedes shoot growth to a greater extent than root growth in all mutants. Moreover, the greater the reduction in GA content the greater the extent of a disturbance at the metabolic level. Low leaf carbohydrate contents were observed in plants displaying higher root growth, suggesting an enhanced flow of photoassimilate to support root growth. Large increases in amino acids contents of either roots or shoot were observed. The increased amino acid content was coupled to reduced levels of TCA cycle intermediates suggesting that these changes are directly linked to early reactions of nitrogen assimilation. The combined data are discussed in terms of our current understanding of the interaction between GA and primary metabolism and their crosstalk in environmental responses.
Keywords: Carbon metabolism; Gibberellins; Nitrogen metabolism; Roots; Shoot; Solanum lycopersicum L.